Cognitive and emotional impairments after cutaneous intoxication by CEES (a sulfur mustard analog) in mice. (1st September 2018) - Gros-Désormeaux, Fanny; Béracochéa, Daniel; Dorandeu, Frédéric; Piérard, Christophe
Abstract: Cognitive and emotional disorders have been reported in veterans intoxicated with sulfur mustard (SM) a chemical weapon belonging to the category of vesicating agents. However, the intense stress associated with the SM intoxication may render difficult determining the exact role played by SM intoxication itself on the emergence and maintaining of cognitive disorders. Animal's model would allow overcoming this issue. So far, we presently investigated the cognitive and emotional impact of an acute cutaneous intoxication with CEES (2-chloroethyl ethyl sulfide), a SM analog in C57/Bl6 mice. Our study evidenced that up to 5 days after a single acute neat CEES skin exposure, compared to controls, mice exhibited i) a significant increase in anxiety-like reactivity in an elevated plus-maze and in an open-field tasks and ii) an alteration of working memory in a sequential alternation task. In contrast, mice submitted to intoxication with a diluted CEES solution or hydrochloric acid (HCl) did not show any memory or emotional impairments. Given that, Our data shows that a single local cutaneous intoxication with neat CEES induced long-lasting cognitive and emotional pejorative effects, in accordance with the epidemiological observations in veterans. Thus, the single acute neat CEES cutaneous intoxication in mice could allow studying the sulfur mustard-induced cognitive and emotional disorders and their further counter-measures.